Meningkatkan Motivasi Belajar Siswa dengan Metode Problem Based Learning Berbantuan Media Wordwall Fase E Kelas X SMA Negeri 4 Sintang - Marlina Siti; Nerita Setiyaningtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Indonesian education continues to develop and seeks the right model, thus inevitably undergoing continuous changes. These changes are certainly aimed at guiding the nation's generation towards intellectual intelligence and character intelligence that increasingly align with the values of Pancasila. Changes that are still ingrained in memory and continue to be adjusted in their application are the changes in the curriculum from the 2013 curriculum to the independent curriculum, which then changed its name to the national curriculum. The presence of this curriculum leads to the freedom to learn and the freedom to teach, but at the same time creates sustainable learning activities for educators. Educators must continue to innovate creatively so that the learning applied is in accordance with the conditions of the students and ultimately can be accepted as something meaningful for their lives. Such conditions eventually motivated me to produce this work with the hope of contributing to the improvement of the quality of education at SMA Negeri 4 Sintang. As an educator, I strive to implement a problem-based learning (PBL) model. I consider this model to provide freedom for students to develop all the potential they possess. I attempt to integrate Wordwall media into PBL learning, making the learning activities more enjoyable. This learning media is Android-based, which is a close companion for teenagers/students today. The use of this tool helps students to surf the internet to access a wealth of information relevant to the material presented. It is hoped that the use of this media can inspire and motivate students to build a desire to learn, a desire to express critical thoughts, and also to foster a spirit of cooperation (participation).